1985
DOI: 10.1037/0022-3514.49.5.1266
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal stability of personality traits: A multitrait–multimethod–multioccasion analysis.

Abstract: The longitudinal stability of personality was investigated in a group of several hundred adults who were rated by themselves, their marriage partners, and their acquaintances in 1935-1938 and by themselves and their marriage partners in 1954-1955. For both men and women, there were very similar factorial structures in all five sources of ratings. Individual differences in neuroticism, social extraversion, and impulse control had reasonably high levels of longitudinal stability over a 19-year period. Both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(147 citation statements)
references
References 36 publications
3
141
0
3
Order By: Relevance
“…Second, data from a number of longitudinal studies were published in the 1980s and 1990s showing long-term stability in individual differences for personality traits (Conley, 1985;Costa & McCrae, 1994;Roberts & DelVecchio, 2000). Test-retest correlations on self-report trait scales over periods of the adult life course for as long as 30 years were so robust that one set of authors suggested that William James may have been close to right when he asserted long ago that personality is "set like plaster" after about age 30 (Costa & McCrae, 1994).…”
Section: Principle 2: the Dispositional Signaturementioning
confidence: 99%
“…Second, data from a number of longitudinal studies were published in the 1980s and 1990s showing long-term stability in individual differences for personality traits (Conley, 1985;Costa & McCrae, 1994;Roberts & DelVecchio, 2000). Test-retest correlations on self-report trait scales over periods of the adult life course for as long as 30 years were so robust that one set of authors suggested that William James may have been close to right when he asserted long ago that personality is "set like plaster" after about age 30 (Costa & McCrae, 1994).…”
Section: Principle 2: the Dispositional Signaturementioning
confidence: 99%
“…For example, great tits were studied from juvenile phases to adulthood spanning 2 to 3 year intervals . Humans were studied from childhood to adulthood spanning ages 3 to 21 (Caspi, 2000); so far the longest studied time spans cover up to 45 to 50 years (Conley, 1984(Conley, , 1985Haan, Millsap, & Hartka, 1986;Soldz & Vaillant, 1999). Given the species differences in lifetimes, stabilities from 6 through 20 years of age in rhesus macaques (Suomi et al, 1996) cover similar extended periods of life.…”
Section: Longitudinal Stabilitymentioning
confidence: 99%
“…Variable-and individual-oriented analyses allow for systematic study, for example, of rank-order stability, within-individual and population mean level stability, individual profile stability, and stability of profile type membership (Akse, Hale III, Engels, Raaijkmakers, & Meeus, 2007;Conley, 1985;Biesanz, West, & Kwok, 2003). Such analyses will shed more light on fundamental issues in individual development across the life span in different species (Block, 1971;Magnusson, 1988;Mervielde & Asendorpf, 2000;van Aken, 2008).…”
Section: Variable-oriented and Individual-oriented Concepts Of Longitmentioning
confidence: 99%
“…They have been shown to be robust across a range of different frameworks, populations, and cultures (Barrick & Mount, 1991;Conley, 1983). The Big Five characterizes personality using five different traits (McCrea & Costa, 1999).…”
Section: Introductionmentioning
confidence: 99%